PENDEKATAN EDUKATIF INTERAKTIF DALAM PENCEGAHAN KEKERASAN SEKSUAL PADA ANAK DI KAMPUNG LITERASI PEKIJING - Nafisah, Azkiya; Siregar, Herlina; Fatimah, Nining (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Sexual violence against children is still a serious problem in Indonesia which is influenced by children's low understanding of personal body boundaries and dangerous situations. Therefore, preventive efforts are needed through early education with an approach that is appropriate to the child's characteristics. This activity aims to increase children's understanding and awareness of the prevention of sexual violence through an educational approach based on interactive activities in the Pekijing Literacy Village. The implementation method is carried out through the coordination, implementation and evaluation stages using storytelling, singing and educational games. The target of the activity is school-age children who are given an understanding of private body parts, inappropriate behavior, and how to protect themselves from dangerous situations. The results of the activity show an increase in children's understanding of recognizing private body parts, the ability to identify behavior that leads to sexual violence, and the courage to refuse and report inappropriate actions. The interactive approach is also able to increase children's participation and involvement during the activity. Thus, an educational approach based on interactive activities can be an effective preventive strategy in efforts to prevent sexual violence against children from an early age.